Assessing the relationship between broad gender inequality and the gender unemployment gap: insights from an extensive global macroeconometric panel analysis - Yahya Algül (Discover Sustainability)
Abstract Various labor market policies have been implemented globally to create a more inclusive work environment for women. However, institutional and structural barriers rooted in the socioeconomic and cultural frameworks of countries often impede progress towards this goal, as outlined in Gender Equality Goal Five of the United Nations Development Goals. Gender inequality in employment is a multifaceted issue influenced by socioeconomic and sociocultural factors, which are affected by households, societies, institutions, and states. Consequently, even with a strong legal framework, desired outcomes may not be achieved if the social structure is not supportive. Therefore, institutional and structural factors often manifest as broader gender disparities within societies, leading to a parallel between gender inequality in society and in the workplace. In this context, this study, as far as is known, is the first to estimate the potential relationship between broader societal gender inequality, measured through a composite index including health, education, economic and political empowerment, and the gender unemployment gap. Additionally, in this context, it has been considered as a second model in the relationship between broader societal gender inequality and women's unemployment rate. Using data from 73 countries with varying sociocultural and economic development levels from 1990 to 2022, two models are estimated using the Panel Mean Group Estimator methodology. The findings indicate that as broader gender inequality increases, both female unemployment rates and the gender unemployment gap rise. Therefore, in addition to conventional policies, it is recommended to implement strategies that promote structural changes within society, enhance women's roles and status, and integrate gender equality principles through education.